Germline Mutations in the Kallikrein 6 Region and Predisposition for Aggressive Prostate Cancer. (14th March 2017) - Briollais, Laurent; Ozcelik, Hilmi; Xu, Jingxiong; Kwiatkowski, Maciej; Lalonde, Emilie; Sendorek, Dorota H.; Fleshner, Neil E.; Recker, Franz; Kuk, Cynthia; Olkhov-Mitsel, Ekaterina; Savas, Sevtap; Hanna, Sally; et al.
Abstract : Background: There is a need for markers that can specifically identify individuals at increased risk of harboring aggressive forms of prostate cancer (PCa). Methods: We surveyed the Kallikrein ( KLK ) region ( KLK 1-15) for single-nucleotide polymorphisms (SNPs) associated with aggressive PCa (Gleason Score ≥ 8) in 1858 PCa patients. Discovery cohorts (Swiss arm of the European Randomized Study of Screening for PCa, n = 379; Toronto, Canada, n = 540) and a validation cohort (Prostate, Lung, Colorectal and Ovarian [PLCO] screening trial, n = 939) were analyzed. Fine-mapping within the KLK region was carried out by genotyping and imputation in the discovery cohort, whereas PLCO data were provided through database of Genotypes and Phenotypes ( dbGaP ). The influence of SNPs of interest on biochemical-free survival was evaluated in a cohort of localized PCa from the International Cancer Genome Consortium (ICGC; n = 130) analyzed with next-generation sequencing. Single- and multi-SNP association studies, as well as haplotype analyses, were performed. All statistical tests were two-sided. Results: Several SNPs in very strong linkage disequilibrium in the KLK 6 region and located within the same haplotype (rs113640578, rs79324425, rs11666929, rs28384475, rs3810287), identified individuals at increased risk of aggressive PCa in both discovery (odds ratio [OR] = 3.51–3.64, 95% confidence interval [CI] = 2.01 to 6.36, P = 1.0x10 −5 –8.4x10 −6 ) and validation (OR = 1.89–1.96, 95% CI = 0.99 to 3.71, P = .04–.05) cohorts. The overall test of haplotype association was highly statistically significant in each cohort ( P = 3.5x10 −4 and .006, respectively) and in the three data sets combined ( P = 2.3x10 −5 ). These germline SNPs independently predicted relapse in the ICGC cohort (hazard ratio = 3.15, 95% CI = 1.57 to 6.34, P = .001). Conclusions: Our fine-mapping study has identified novel loci in the KLK 6 region strongly associated with aggressive PCa.